2012
DOI: 10.1186/ar3928
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte populations as markers of response to adalimumab plus MTX in rheumatoid arthritis

Abstract: IntroductionThe treatment of rheumatoid arthritis (RA) patients with anti-tumor necrosis factor alpha (TNFα) biological drugs has dramatically improved the prognosis of these patients. However, a third of the treated patients do not respond to this therapy. Thus, the search for biomarkers of clinical response to these agents is currently highly active. Our aim is to analyze the number and distribution of circulating monocytes, and of their CD14+highCD16-, CD14+highCD16+ and CD14+lowCD16+ subsets in methotrexat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
2
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 37 publications
4
32
2
1
Order By: Relevance
“…The expression of CD18 was stronger on CD163 + than CD163 - monocytes ( P <0.001). Confirming the finding from previous studies of arthritis [7-9], there were a non-significant, greater proportion of intermediate monocytes among all monocytes in HLA-B27-negative SpA patients compared with HCs (Figure 6C). A positive correlation was observed between the proportion of non-classic (Figure 7A) and intermediate (Figure 7B) monocytes among all CD14 + monocytes and the concentration of sCD18 in the PBMC culture supernatants, whereas a negative correlation was found for the proportion of classic monocytes (Figure 7C).…”
Section: Resultssupporting
confidence: 91%
“…The expression of CD18 was stronger on CD163 + than CD163 - monocytes ( P <0.001). Confirming the finding from previous studies of arthritis [7-9], there were a non-significant, greater proportion of intermediate monocytes among all monocytes in HLA-B27-negative SpA patients compared with HCs (Figure 6C). A positive correlation was observed between the proportion of non-classic (Figure 7A) and intermediate (Figure 7B) monocytes among all CD14 + monocytes and the concentration of sCD18 in the PBMC culture supernatants, whereas a negative correlation was found for the proportion of classic monocytes (Figure 7C).…”
Section: Resultssupporting
confidence: 91%
“…Neutrophil granule genes exhibited higher expression in nonresponders than in responders before treatment with anti‐TNF agents . Monocyte numbers have been reported to be higher in nonresponders than in responders after 3 or 6 months of anti‐TNF treatment . These results suggest enhanced activity of alternative immune pathways in anti‐TNF‐IR patients that may be targeted for clinical improvement.…”
Section: Discussionmentioning
confidence: 95%
“…The main findings of this study are that patients with IIM have an expansion of circulating intermediate monocytes and that their monocytes subsets have a differential expression of TLR4 and TLR2, which correlate with serum IL-6, as well as with distinctive clinical features. Previously, it was shown that anti-TNF therapy is able to reduce the expression of TLRs in monocytes from patients with rheumatoid arthritis (RA) and spondylarthopathy [27,28]. Nevertheless, most studies have demonstrated that immunosuppressive therapy does not have an effect in the proportion of monocyte subsets, as shown in patients with RA under methotrexate treatment [29] and in patients with solid organ transplantation [30].…”
Section: Discussionmentioning
confidence: 99%